Neurological examination of small ruminants - GIADINIS (Ν. Δ. ΓΙΑΔΙΝΗΣ) N. D.; PANOUSIS (Ν. Κ. ΠΑΝΟΥΣΗΣ) N. K.; POLIZOPOULOU (Ζ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H. (Journal of the Hellenic Veterinary Medical Society, 2017)
The neurological examination in small ruminants is very helpful in confirming the presence of a neurological problem and localizing the site of the lesion. The anatomical localization is useful for the differential diagnosis, prognosis and treatment of neurological diseases. A thorough review of the case history and clinical examination are followed by the inspection from a distance in order to assess behavior, level of consciousness and position of head, trunk and limbs. The locomotion disorders are evaluated upon walking the animals. Proprioception is examined with the postural reactions and cranial nerve function with the testing of the appropriate reflexes. The neurological examination is completed with the evaluation of muscular tone, spinal reflexes and the assessment of superficial and deep pain sensation.